Autonomous Portable Solar Ultraviolet Spectroradiometer (APSUS) – a New CCD Spectrometer System for Localized, Real‐Time Solar Ultraviolet (280–400 nm) Radiation Measurement. (10th March 2014) - Hooke, Rebecca; Pearson, Andy; O'Hagan, John
Abstract Terrestrial solar ultraviolet (UV) radiation has significant implications for human health and increasing levels are a key concern regarding the impact of climate change. Monitoring solar UV radiation at the earth's surface is therefore of increasing importance. A new prototype portable CCD (charge‐coupled device) spectrometer‐based system has been developed that monitors UV radiation (280–400 nm) levels at the earth's surface. It has the ability to deliver this information to the public in real time. Since the instrument can operate autonomously, it is called the Autonomous Portable Solar Ultraviolet Spectroradiometer (APSUS). This instrument incorporates an Ocean Optics QE65000 spectrometer which is contained within a robust environmental housing. The APSUS system can gather reliable solar UV spectral data from approximately April to October inclusive (depending on ambient temperature) in the UK. In this study the new APSUS unit and APSUS system are presented. Example solar UV spectra and diurnal UV Index values as measured by the APSUS system in London and Weymouth in the UK in summer 2012 are shown.